Systems approaches to study root architecture dynamics - Cuesta, Candela; Wabnik, Krzysztof; Benková, Eva (Frontiers in Plant Science, 2013)
The plant root system is essential for providing anchorage to the soil, supplying minerals and water, and synthesizing metabolites. It is a dynamic organ modulated by external cues such as environmental signals, water and nutrients availability, salinity and others. Lateral roots are initiated from the primary root post-embryonically, after which they progress through discrete developmental stages which can be independently controlled, providing a high level of plasticity during root system formation. Within this review, main contributions are presented, from the classical forward genetic screens to the more recent high-throughput approaches, combined with computer model predictions, dissecting how lateral roots and thereby root system architecture is established and developed.